Rethinking NGOization as Postfeminist Practice: Interstitial Intimacies and Negotiations of Neoliberal Subjectivity in Violence Prevention - Chakraborty, Proshant (Frontiers in Sociology, 2021)
The decade of the 1990s marked the rise of postfeminism, a series of discursive, mediatized and intellectual interventions that furthered, but also broke away from, past forms of feminist mobilizations and theories. This period also witnessed the global proliferation of non-governmental organizations (NGOs) and the “NGOization” of feminism, referring to the cooption and erasure of critical social movements. Beyond on their temporal instantiation in the 1990s, postfeminism and NGOization share crucial points of convergence in everyday practices of women’s NGOs and organizations. In this article, I examine such convergences as they unfold in a community-based intervention program to prevent violence against women and girls in Mumbai’s urban poor neighborhoods. Such programs create new forms of femininity and womanhood among women who become part of such interventions as frontline workers. These women navigate complex pressures of communitarian gender norms, disciplinary regimes of professionalization and quantification, and the vicarious harm of supporting survivors. Their affective caring labor, thus, is facilitated by and produces what I describe as interstitial intimacies, which problematize and embody key postfeminist claims, while engendering political actions and contestations under neoliberalism.